Breastfeeding, a child survival strategy against infant mortality in Nigeria - Jacdonmi, Itse; M. S., Suhainizam; G. R., Jacdonmi (Scientific Publishers, 2016)
Babies grow and develop best when they are breastfed exclusively. Much emphasis has been placed on exclusively breastfeeding an infant during the first six months after birth. However, many women especially in the developing countries continue to introduce complementary feeding before the first six months. In Nigeria, high infant mortality rate still remains a major issue of concern. Several studies indicate that the cause of childhood mortality is due to lack of proper breastfeeding. In this review, we focus on the trends and patterns of breastfeeding, causes of infant mortality and breastfeeding of infants from birth to six months, followed by appropriate and adequate complementary feeding for two years and above, as a strategic intervention against infant mortality and the need to create awareness about the benefits of breastfeeding.